The Impact of workplace challenges on Suicidal ideation among Correctional Officers - Mohd Razali, Otman (University Malaysia Sarawak, 2024)
This study aims to investigate the impact of workplace challenges on suicidal ideation among correctional officers in Malaysia. There were 258 correctional officers involved in this study. The respondents were selected by using the cluster random sampling technique. This study utilised the quantitative research design. Employee’s problems were assessed by using the Employee Needs Assessment Inventory (ENAI), and suicidal ideation was based on the Interpersonal Needs Questionnaire (INQ). Pearson Product Moment Correlation Coefficient and ,ultiple Regression are used to analyse the results of this study. Based on the findings, there was a significant correlation between personal-related problems (health, financial, family) and suicidal ideation, (r = .444, N = 258, p < .05), work-related problems (work, interpersonal relationship, work environment) and suicidal ideation, (r = 331, N = 258, p < .05. Other problems that contributed to the significant correlations of suicidal ideation were health, financial, family, work, interpersonal relationship and work environment, r=.444; p<.05, r=323; p<.05, r=281; p<.05, r=330; p<.05, r= 262; p<.05, r=276; p<.05 respectively. Multiple regression analysis reported that personal problems influenced suicidal ideation (R2 = 20, F (1, 256) = 62.867, p < .05). The work-related factors also influenced suicidal ideation (R2 = 11, F (1, 256) = 31.31, p < .05). In conclusion, the implications of the research were divided into two categories, the theoretical and practical implications. In terms of theoretical implication, the model underlying the research signified that employee problems indicate a significant positive relationship with suicidal ideation. Practically, exploring and understanding employee problems can guide the development of interventions in tackling these issues. Future studies could also be performed across different industries and areas of work to widen this study's scope.